Biocontrol of Cosmopolites sordidus using entomopathogenic fungi under laboratory conditions, Ecuador - Valdez, Danilo; Farah, Simón; Espinoza, Winston; Veliz, Freddy; Villon, Henry; Herrera, Liliam (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Cosmopolites sordidus known as the black weevil, is an insect pest of economic importance for Musaceae crops such as bananas and plantain, resulting in production losses due to its damage. One of the alternatives for the management of the black weevil is biological control using entomopathogens that regulate the insect populations in Musaceae plantations. The objective of the research was to determine the action of the entomopathogenic fungi Beauveria bassiana, Metarhizium anisopliae, and Verticillium lecanii on adults of the black banana weevil under controlled laboratory conditions. A completely randomized design was implemented with 8 treatments with the application of the entomopathogens individually and in combinations, as well as a control treatment. The results showed that the treatment with the combination of B. bassiana + M. anisopliae showed the best control of the insect pest with 100 % mortality 10 days after inoculation, followed by B. bassiana with 88 % and 24% control with M. anisopliae, while the treatment with the fungus V. lecanii achieved 32 % control of the black weevil. Entomopathogens are an alternative for the management of the insect pest of Musaceae C. sordidus.